ANALISIS PERUBAHAN KECEPATAN SPINDLE TERHADAP KEKASARAN PERMUKAAN DAN KEAUSAN PAHAT PADA PEMBUBUTAN BAJA AISI 4340 - Manta, Faisal; Artika, Kurnia Dwi; Radyantho, Kholiq Deliasgarin; Taufiq (POLITALA PRESS, 2024)
The cutting quality of a lathe is influenced by various cutting parameters. Spindle speed is the main parameter that influences the level of surface roughness and tool wear. The research aims to understand the impact of using a VNMG 160408-MA type insert tool in cutting AISI 4340 steel on surface roughness and tool wear values. The spindle speeds used are 190 rpm, 300 rpm, 460 rpm, 755 rpm, 1,255 rpm, feed rate 0.209 mm/rev, and cutting depth 0.5 mm. Experimental methods were used in the research. The research results showed that variations in spindle speed had a significant effect on surface roughness, tool wear and cutting temperature as evidenced by the P-Value < 0.05. At a value at a spindle speed of 190 rpm, the surface roughness value was 6.195 μm, tool wear was 0.002 grams and tool temperature was 48.178 °C. The spindle speed value of 1,255 rpm measured a surface roughness value of 1.971 μm, tool wear of 0.053 grams, and tool temperature of 90.389 °C.